(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
A comparative cross sectional study was conducted to find out an association between anxiety and smoking. This study provides information about impact of smoking and anxiety on smokers and non smokers. Anxiety related information was collected by using an anxiety determinate scale. A total of 20 questions were scored on the scale. Scoring was done according to a set standard system. Among 110 smoker, 85 (77.3%) had no anxiety, 15 (13.6%) had mild anxiety, 6 (5.4%) moderate anxiety and the rest 4 (3.7%) had severe anxiety. Among 110 non smokers 96 (87.3%) had no anxiety, 9 (9%) had mild anxiety, 3 (3%) moderate and the rest 2 (1.8%) had severe anxiety. Among 39 anxiety disorder respondents, 25.6% had anxiety for 2 months, 46.2% had anxiety for 6 months & 28.2% had anxiety which lasted for more than a year. Among 39 anxiety disorder respondents, 43.5% had anxiety disorders in other family members. Anxiety was mostly seen in the smoker groups. Association between smoking habit of the respondents was an important determinant to have anxiety. There were significant correlation between smoking and anxiety J. Dhaka National Med. Coll. Hos. 2013; 19 (01): 17-22